Os movimentos negros e as políticas públicas para a educação no Brasil e no Uruguai após a Conferência de Durban - Jesus, Fernando Santos de (2020)
This study is focused on public education policies for black populations in Brazil and Uruguay, developed after the third United Nations World Conference against Racism, RacialDiscrimination, Xenophobia and Related Intolerance held in Durban, South Africa, in 2001. Our research is based on the voices of administrative technicians of the 2016 management of the Secretariat for Continuing Education, Literacy, Diversity and Inclusion – SECADI, and activists of black movements who participated in the Durban Conference and/or who are administrative technicians in agencies responsible for public policy development. We realized a literature review on the subsequent topics: racism; Durban conference; institutional racism and history of Uruguay. It is noteworthy that in order to carry out this research, it was necessary to conduct semi-structured interviews with the aforementioned persons. Through the analysis of the interviews, we explored the history of black movements as well as the difficulties and political constraints to implement public education policies that benefit the black population in these countries. In Brazil, the Durban conference led to the creation of SECADI, indicating an important achievement of the black movement in the fight against racism. Likewise, we found that in Uruguay the greatest accomplishment with regard to public policies aimed at the black population was attained after Durban. Law 19.122/06 is a historical remark in the country and its implementation was guided by the struggle of black movement activists who participated in the Durban conference. Therefore, we conclude that the third UN World Conference against Racism, Racial Discrimination, Xenophobia and Related Intolerance was a historical remark in which the agendas of black movements from Brazil and Uruguay converged, addressing historical questions through public policies like those in the field of education analyzed in this study.